Case report Spinal accessory nerve meningioma in a paediatric patient: Case report - Liechty, Peter; Tubbs, Shane; Loukas, Marios; Blount, Jeffrey P.; Wellons, John C.; Acakpo-Satchivi, Leslie; Oakes, Jerry W.; Grabb, Paul A. (Folia Neuropathologica, 2007)
Accessory nerve meningiomas are exceedingly rare. We present a case of a nine-year-old patient with neurofibromatosis type 2 who had radiologic evidence of spinal cord compression from an upper cervical/foramen magnum lesion. He was asymptomatic from this lesion, but it progressed in size. The tumor was resected and histologic investigation revealed frequent tight whorls and psammoma bodies consistent with meningioma. To the authors’ knowledge, this is the first reported spinal accessory nerve meningioma in a pediatric patient.